The Impact of Migration Policies on Rural Household Welfare in Mexico and Nicaragua - Taylor, J. Edward (OECD Development Centre Working Papers, 2011)
This working paper presents findings from an effort to evaluate the impacts of immigration policies on the welfare of migrants and their families in migrant-sending countries. It uses a disaggregated micro economy-wide modelling approach, designed to capture both the potentially positive and negative effects of migration and remittances in migrant-sending areas and the complex processes shaping these impacts. The model is used to explore the possible effects of destination-country immigration policies on rural welfare in Mexico and Nicaragua (US policies in the first case and US and Costa Rican policies in the second). The findings highlight the sensitivity of sending-country welfare to immigration policies, not only in the households that send migrants and receive remittances but other households with which they interact within the migrant-sending economy. Impacts vary between the two countries and across households, and they also depend upon the gender and skills of migrants. The paper concludes by discussing the importance of both destination and source country policies in shaping the impacts of international migration on rural welfare